Double lumen tube: Size and insertion depth - Abdelazeem A Eldawlatly (Saudi Journal of Anaesthesia, 2021)
Double lumen tubes (DLTs) are most commonly used to achieve one lung ventilation (OLV) in most thoracic surgical procedures unless contraindicated. Left-sided DLT (LDLT) is most commonly used nowadays for most thoracic surgical procedures. Though, the use of LDLT dates long back in history, two clinical and technical issues are yet to be resolved. The first issue is the ideal size of DLT which is defined as that which provides near-complete seal of the bronchial lumen without cuff inflation. There are no guidelines in literature which help in selecting the size of DLT. However, general consensus among thoracic anesthesiologists recommends the use of smaller sizes to avoid airway trauma. In our practice and for the last few years, we are using smaller size LDLT 35 F for females and 37 F for males with minimal airway trauma and had encouraging results. The second issue is the insertion depth of the LDLT. We have introduced a height-based formula to predict the insertion depth of LDLT with encouraging results. However, even with the use of the formula, we still recommend the use of fiberoptic bronchoscopic confirmation method for final positioning of the LDLT.